CONSUMO DE ETANOL EM BINGE PREJUDICA A MEMÓRIA OPERACIONAL ESPACIAL DE RATOS ADOLESCENTES E JOVENS ADULTOS - Santos, Matheus Cavatti (2020)
Disorders in alcohol consumption are one of the main risk factors for the development of neurological disorders worldwide. The partial and incomplete full development of the central nervous system during adolescence, especially of the prefrontal cortex (P